Identification of new endocrine disruptive transthyretin ligands in polluted waters using pull-down assay coupled to non-target mass spectrometry - Mikušová, P; Toušová, Z; Sehnal, L; Kuta, J; Grabicová, K; Fedorova, G; Marek, M; Grabic, R; Hilscherová, K (Journal of hazardous materials, 2024)
Surface and treated wastewater are contaminated with highly complex mixtures of micropollutants, which may cause numerous adverse effects, often mediated by endocrine disruption. However, there is limited knowledge regarding some important modes of action, such as interference with thyroid hormone (TH) regulation, and the compounds driving these effects. This study describes an effective approach for the identification of compounds with the potential to bind to transthyretin (TTR; protein distributing TH to target tissues), based on their specific separation in a pull-down assay followed by non-target analysis (NTA). The method was optimized with known TTR ligands and applied to complex water samples. The specific separation of TTR ligands provided a substantial reduction of chromatographic features from the original samples. The applied NTA workflow resulted in the identification of 34 structures. Twelve compounds with available standards were quantified in the original extracts and their TH-displacement potency was confirmed. Eleven compounds were discovered as TTR binders for the first time and linear alkylbenzene sulfonates (LAS) were highlighted as contaminants of concern. Pull-down assay combined with NTA proved to be a well-functioning approach for the identification of unknown bioactive compounds in complex mixtures with great application potential across various biological targets and environmental compartments.
Keywords: Wastewater; Thyroid hormone signaling; prealbumin; Endocrine Disruptors; Water Pollutants, Chemical; Ligands; Mixtures; endokrinní disruptory; odpadní voda; ligandy; Protein expression; Prealbumin; hmotnostní spektrometrie; chemické látky znečišťující vodu; Mass Spectrometry; Affinity purification